Campylobacter jejuni ST50, a pathogen of global importance: A comparative genomic analysis of isolates from Australia, Europe and North America. (27th May 2021) - Wallace, Rhiannon L.; Cribb, Danielle M.; Bulach, Dieter M.; Ingle, Danielle J.; Joensen, Katrine G.; Nielsen, Eva Møller; Leekitcharoenphon, Pimlapas; Stingl, Kerstin; Kirk, Martyn D.
Summary: Campylobacter jejuni is the leading cause of bacterial gastroenteritis globally, and infections are often transmitted through consumption of raw or undercooked poultry. Campylobacter jejuni ST50 is among the top ten sequence types (STs) reported in the collected isolates listed at PubMLST records from poultry, food and clinical sources for Asia, Europe, North America, Oceania and South America. This study was designed to determine the most commonly reported C. jejuni STs globally using the PubMLST database and assess similarities between genomes of C. jejuni ST50 isolates from geographically distinct locations. To gain a better understanding of C. jejuni diversity, we compared draft genome sequences of 182 ST50 isolates recovered from retail or caecal poultry samples in Oceania, Europe and North America that were collected over a period of 9 years (2010 to 2018). Overall, phylogenetic analysis revealed that isolates from geographically distinct locations tended to cluster based on the continent where the sample was collected. Among ST50 isolates from Europe and North America, we identified resistance determinants associated with phenotypic resistance to beta‐lactams (EU: 55%; GB: 43.1%), tetracyclines (CA: 77.3%; EU: 37.5%; GB: 9.8%; US: 43.5%) and fluoroquinolones (EU: 60.0%; GB: 15.7%); no resistance determinants were identified in isolates from Australia. In general, the majority of the virulence genes, with rare exceptions such as wlaN, cj1138, hddA and rfbC, were evenly distributed throughout the genomes of all ST50 isolates in this study. Genomic‐based characterization of C. jejuni ST50 isolates from poultry on three continents highlighted that geographically distinct isolates have evolved independently but only represent a glimpse into the diversity of C. jejuni .